PENERAPAN SISTEM PEMBIAYAAN JAMINAN EMAS PADA BMT UGT NUSANTARA CAPEM BLEGA KABUPATEN BANGKALAN - Kulsum, Ummi; Rohman, Saiful; Anifah, Siti (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to find out how the implementation of the gold guarantee financing system at BMT UGT Nusantara capem Blega, Bangkalan Regency. This research uses a qualitative type of research. Data sources in this study are primary and secondary data. The data collection techniques used are observation, interviews and documentation.The results of this study explain that the financing product of BMT UGT Nusantara that can be used as an alternative to meet the need for cash quickly and easily is Gold Guarantee Financing abbreviated as PJE. This product uses the contract Rahn Bil Ujrah. In this financing there are special requirements given to prospective customers. Among them, for goods / gold that want to be used as collateral as financing must be in the form of real gold, both old gold and young gold. The gold valuation stage of BMT UGT Nusantara capem Blega Adjust to market prices. Furthermore, in the repayment stage, customers can pay off their loans at any time without waiting for maturity. And lastly, in the auction stage. BMT UGT Nusantara Capem Blega does not arbitrarily auction collateral, but must fulfill several auction procedures set by BMT UGT Nusantara. Keywords: Financing, Gold Guarantee, B